Isolement et caractérisation des bactéries lactiques à partir du smen traditionnel Algérien - LIDRICI, NARIMANE; BELMADI, ASMAA (My University, 2020)
The microbial microflora of raw milk traditional dairy products composed mainly of lactic acid bacteria, the latter play an important role in the organoleptic characteristics of fermented dairy products. Smen is a traditional dairy product widely consumed by the Algerian population. This work is interested in identifying the lactic flora isolated from this traditional product and then studding some technological aptitudes of the identifiedstrains. Lactic strains were isolated from three samples of a traditional dairy product collected from different regions « El Sahara, Djelfa and Jijel » and identified phenotypic ally on the basis of physiological and biochemical tests as well as on the basis of their fermentation profiles by API 20 E and API 50 CHL galleries. With regard to technological aptitudes, three activities were carried out: Acidifying, proteolytic and texturizing activity. Identification revealed the presence of the following genera: Lactococcus, Lactobacillus, Leuconostoc and Enterococcus. The results of the technological aptitudes show thatonly the strains of the genus Leuconostoc have the capacity to produce exopolysaccharides and the strains of the other genera tested show good acidifying activity with varying values of (18 to 110.20 oD) and good proteolytic activity (zone lysis varied from 5 to 7 mm).
Keywords: Smen; Lactic acid bacteria; technological skills.